Academic Writing for Publication Purposes: The Infelicities of Style - O. L. Dobrynina (Высшее образование в России)
Low level of literacy of students, postgraduate students and university staff results in infelicities of style in Russian scientific papers and abstracts that might lead to manuscript rejection for publication in international journals. The author addresses the task of readability improvement of abstracts and scientific papers written by university staff members from technical and natural sciences departments. Sentence and text readability is determined not only by the number of words, i.e. the length of a sentence but also by the sentence structure and its grammar and lexical structure. The infelicities of style are caused by differences in scientific discourse between Russian and English languages. In particular, these might be nominalization, complex sentence structure, and wide use of Passive Voice in Russian sentences. Bilingual education is considered as the process of trainees’ introduction to the English-speaking world culture based upon matching Russian and English stylistic features. As the result the trainees realize the necessity of pre-translation adaptation of their texts. The author suggests some ways of pre-translation preparation of a sentence: shortening the sentence length up to 10-20 words by eliminating non-informative words and splitting a complex sentence into two or three according to the rule: one idea = one sentence. Some examples illustrate how chains of nouns in the genitive case could be substituted with other structures. Special attention is paid to parallel structures usage and eliminating non-informative words. In this way Russian authors will be able to write concise and clear texts in Russian and English in accordance with the accepted international language conventions.